Exploring Viral–Host Protein Interactions as Antiviral Therapies: A Computational Perspective - Idrees, Sobia; Chen, Hao; Panth, Nisha; Paudel, Keshav Raj; Hansbro, Philip M. (Microorganisms (Basel), 2024)
The interactions between human and viral proteins are pivotal in viral infection and host immune responses. These interactions traverse different stages of the viral life cycle, encompassing initial entry into host cells, replication, and the eventual deployment of immune evasion strategies. As viruses exploit host cellular machinery for their replication and survival, targeting key protein–protein interactions offer a strategic approach for developing antiviral drugs. This review discusses how viruses interact with host proteins to develop viral–host interactions. In addition, we also highlight valuable resources that aid in identifying new interactions, incorporating high-throughput methods, and computational approaches, ultimately helping to understand how these tools can be effectively utilized to study viral–host interactions.